Closer to or further from the new normal? business approach through social media analysis - Iglesias-Sánchez, Patricia Pilar; Jambrino-Maldonado, Carmen; De-las-Heras-Pedrosa, Carlos; Fernández-Díaz, Elena (Elsevier/Cell Press, 2021)
The outbreak of COVID-19 has led to radical change in all social and economic spheres and, even today, the scope of the pandemic cannot be detailed. This unprecedent situation is challenging the global world but particularly for business. The packages of measures internationally imposed as restrictions on commercial activity, isolation and social distancing mean that business should face a transformation in order to survive in each stage of the crisis. For this purpose, a content analysis with an initial dataset with 2,610 tweets of the most representative Spanish entrepreneurial organizations was carried out in key periods of the pandemic. The findings highlight that there are collective concerns with emotional burden in the business sector that encourage action despite confusion and uncertainty. Generalized distrust of policies led business organizations to insist on innovation and adaptation as the best tools to overcome the economic effect of the crisis.
Keywords: COVID-19 - Aspectos económicos; COVID-19; Social media; Business; Economic effect; New normal